Microdosimetric study for helium-ion beam using fully 3D silicon microdosimeters. (October 2020) - Lee, S H; Mizushima, K; Sakata, D; Kohno, R; Sakama, M; Iwata, Y; Shirai, T; Pan, V A; Tran, L T; Rosenfeld, A B; Suzuki, M; Inaniwa, T
Abstract: In this study, the survival fraction of pancreatic cancer cells exposed to a spread-out Bragg peak (SOBP) helium-ion beam are estimated using the microdosimetric method with the microdosimetric kinetic (MK) model, by measuring the specific energy with a microdosimeter. To measure the microdosimetric spectra, a 3D mushroom microdosimeter was used by mounting it on silicon-on-insulator (SOI) substrates. At different positions of the Bragg curve of a pristine helium-ion beam of 166 MeV/u, microdosimetric spectra were measured via a scanning beam port in the National Institute of Radiological Sciences. The MK parameters were determined such that the survival fraction (SF) calculated by the MK model predicts the previously reported in vitro data. For a cuboid target of 10×10×6 cm3, a treatment plan that utilised helium-ion beam was designed from the in-house treatment planning software (TPS) to achieve a 10% SF of pancreatic cancer cells throughout the target. The physical doses and microdosimetric spectra were measured for different depths by irradiating the scanning-SOBP helium-ion beam; consequently, the SF at each position of the SOBP was predicted. The predicted SFs from measured physical dose and microdosimetric spectra were in good agreement with the planned SF from TPS.